ETIKA KERJA DALAM ORGANISASI PENDIDIKAN - Zatria Jabar Anggoro; Nida Sabastiani Aulia; Putri Kaisa Rachmani (CV. Denasya Smart Publisher, 2026)
Work ethics is a fundamental aspect in supporting the success of educational organizations, as it is not only related to compliance with rules but also reflects moral values, integrity, and the professional responsibility of educators. Although various studies have examined work ethics from different perspectives, studies that comprehensively integrate its determinants, roles, and impacts within educational organizations across different levels remain limited, particularly those employing a Systematic Literature Review (SLR) approach. This study aims to identify and map the factors influencing work ethics, as well as its impact on performance and organizational culture in educational institutions, using an SLR approach guided by the PRISMA framework. Data were collected from relevant scientific journals and analyzed using content analysis techniques to identify themes, patterns, and relationships among concepts. The findings indicate that work ethics in educational organizations is influenced by internal factors (motivation, personality, and professional ethics) and external factors (organizational culture, work environment, reward systems, and institutional support), which interact to form three main clusters: educator professionalism, learning quality, and student character. Conversely, low work ethics not only reduces the quality of learning and the professional image but also triggers psychological pressure and role conflict among educators. This study contributes to the development of a conceptual framework of work ethics in educational organizations through the integration and mapping of factors from various literature sources. However, this study is limited to a literature review and does not include empirical validation or testing of relationships between variables. Therefore, future research is recommended to adopt an empirical approach in order to obtain more in-depth findings regarding work ethics in educational organizations.